Performance Assessment Berbasis Model Problem Based Learning sebagai Alternatif untuk Mengukur Keterampilan Berpikir Kritis Siswa SMP - Paramitha, Widya Ayu; Nurwahyunani, Atip; Mulyaningrum, Eko Retno; Jamali, Jamali (Bioma : Jurnal Ilmiah Biologi, 2023)
PBL based performance assessment involves students directly and can train them to face various problems and find solutions to problems. Science learning in class VIII shows that critical thinking skills are still relatively lacking in the process of discovering concepts in the material and the ability to answer questions based on critical thinking skills. The low level of critical thinking skills is caused by students lack of conceptual discovery of the material being taught and examining the relationship between the material and solving problems in daily life, which is done directly through performance assessments, which were previously rarely implemented in the classroom. The PBL syntax embedded in the performance assessment rubric is also integrated with the critical thinking skills component. The aim of this research is to find out whether PBL-based performance assessment can be used to measure students' critical thinking abilities. This research uses a qualitative research method with a case study approach with descriptive data explanation in class VIII D of SMPN 37 Semarang. Students are asked to develop critical thinking skills through group work, with the results of practical and product performance assessment activities showing a good category. Where the practice percentage shows the lowest value with a percentage of 50% in the deduction dimension, with activities to determine conclusions and consider the results of the analysis with problems in each group to answer questions. The percentage of practice shows the highest score with a percentage of 75% in the dimensions of inference, recognition and interpretation with information analysis activities, exploration of information and conditions, identification of information obtained, presenting solutions and preventive efforts and the results of group work.